2010
DOI: 10.1590/s1516-35982010000300018
|View full text |Cite
|
Sign up to set email alerts
|

Bionutritional efficiency of crossbred beef cattle finished on feedlot andslaughtered at different body weights

Abstract: -The objective of this study was to assess the bionutritional efficiency of crossbred F1 Red Angus × Nellore (½ RA ½ N) and F1 Blonde D'Aquitaine × Nellore (½ BA ½ N) young bulls finished on feedlot and slaughtered at 480, 520 and 560 kg body weight. A completely randomized experimental design in a 2 × 3 (genetic group × slaughter weight) factorial arrangement with six replicates was used. The ½ BA ½ N young bulls showed higher kidney, pelvic and inguinal fat (KPIF, kg and % BW) and lower multivariate biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
1
5
0
1
Order By: Relevance
“…These negative numbers are incoherent biological values for FCR and FEI calculation, but BNI combines feed intake and weight gain into a new one-dimensional variable that encompasses their characteristics and prevents these problems (GUIDONI, 1994;DETMANN et al, 2005). This tool has been used to analyze the nutritional efficiency of high performance farm animals (EUCLIDES-FILHO et al, 2001;DETMANN et al, 2005;MELLO et al, 2010) and in this study we found that it is also valuable to assess the effects of parasitic infections on nutritional development, especially when there are no clinical signs.…”
Section: Discussionmentioning
confidence: 90%
“…These negative numbers are incoherent biological values for FCR and FEI calculation, but BNI combines feed intake and weight gain into a new one-dimensional variable that encompasses their characteristics and prevents these problems (GUIDONI, 1994;DETMANN et al, 2005). This tool has been used to analyze the nutritional efficiency of high performance farm animals (EUCLIDES-FILHO et al, 2001;DETMANN et al, 2005;MELLO et al, 2010) and in this study we found that it is also valuable to assess the effects of parasitic infections on nutritional development, especially when there are no clinical signs.…”
Section: Discussionmentioning
confidence: 90%
“…After that, the non-normalized eigenvectors associated with 1 (higher eigenvalue) were esti by solving the equations: GUIDONI, 1994;MELLO et al, 2010). The analy variance was performed using PROC GLM.…”
Section: Ingredientsmentioning
confidence: 99%
“…After that, the non-normalized eigenvectors associated with 1 (higher eigenvalue) were estimated by solving the equations: , where VC 1 is the first canonical variable, Y is animal transformation (ADG, kg day -1 ), X is the DMI (kg day -1 ), and and are defined above. The values of this function were denominated multivariate biological nutritional index -MBNI (GUIDONI, 1994;MELLO et al, 2010). The analysis of variance was performed using PROC GLM.…”
Section: Ingredientsmentioning
confidence: 99%
See 2 more Smart Citations